Eco-Pesantren Management Based on Hifzul Bī’ah for Sustainable Islamic Education - Sulaeman Sulaeman; Ferdinan Ferdinan; Abd. Rahman (Nidhomiyyah: Jurnal Manajemen Pendidikan Islam, 2026)
The research aims to analyze how environmental values are integrated into pesantren management and how this contributes to cultivating ecological awareness among students. A qualitative case study approach was employed, involving in-depth interviews, participatory observation, and document analysis. Data were analyzed using Miles and Huberman’s interactive model, consisting of data reduction, display, and conclusion drawing. The findings indicate that eco-pesantren management is manifested through the alignment of institutional policies, spiritual guidance, and structured environmental programs. Each division holds ecological responsibilities, supported by monitoring mechanisms and routine evaluations. Leadership plays a central role in reinforcing environmental values through participatory policies and modeling behavior. Active student engagement in daily sanitation routines fosters environmental literacy, spiritual discipline, and sustainable behavior. Challenges include limited green space and lack of environmental education training among teachers. This study demonstrates that Hifzul Bī’ah can be systematically operationalized within Islamic education to promote sustainable culture. It contributes to the discourse on Islamic educational management and offers a model for integrating faith-based values in environmental sustainability initiatives.